Una nueva especie neotropical de Termitomyces (Agaricales: Tennitomycetaceae) - Gómez P., Luis Diego (Universidad de Costa Rica, 1994)
A new species of Costa Rican agarics is described: Termitomyces dominicalensis. This constitutes the first neotropical record of this predominantly paleotropical genus. The new species inhabits the arboreal and epigean nests of Nasutitermes comiger (Isoptera: Termitidae) in the Pacific coastal lowlands. Sorne new cornbinations are proposed for names previously assigned to Podabrella Singer.